(untitled) (Acta Scientiarum. Agronomy, 2011)
A knowledge of rainfall time distribution is important for several types of hydrological studies related to surface runoff. This study aims to determine the time distribution pattern of heavy rain events in Urussanga, Santa Catarina State, Brazil. It employed recording rainfall charts from the meteorological station of Urussanga (latitude: 28.31° S, longitude: 49.19° W, altitude: 49 m) from 1980 to 2007. Rain events were classified into four types according to the duration quartile in which the greatest amount of precipitation occurred. It is found that type I rain events are more frequent, followed by type II, and these occur predominantly during the summer, while type III and IV rain events are distributed throughout the year. In the summer, rain events that last for less than 12 hours are more frequent, whereas during the rest of the year, rain events that last for more than 18 hours are most common.